Konkurencyjność przedsiębiorstw w świetle wymagań rozwoju trwałego i zrównoważonego - Adamkiewicz-Drwiłło, Hanna; Kruk, Hanna; Skrzeszewska, Katarzyna (Business Competitiveness in the Light of Sustainable Development, 2008)
Competitiveness is often defined (in general way) as a business ability to stay on the market. Nowadays the sustainable development concept gains more and more adherents. In changeable surroundings, the environment, as a development factor, becomes more important. Businesses, during planning their activities, have to take into account problems of the environment protection. For many of them, these problems are development barrier, but other businesses consciously decide on using "green" (environment friendly) technologies, and they built their competitive advantage on this strategy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 11-20